Pandangan Hukum Islam Tentang Arisan Haji - Irdlon Sahil (STAI Syaichona Moh. Cholil Bangkalan, 2015)
Arisan Hajj is a ceremony performed by some Muslims whovolunteered to work together to save money in the agreed amount to pay thecost of Pilgrimage (ONH) alternately among members. In this case thegathering that aims to dispatch members to go on Hajj, of course, based onagreements and regulations made together. And this is where problems ariserelating to the Hajj gathering istito'ah impose as a mandatory requirementpilgrimage. In general, the law of the Hajj gathering there are two opinions,namely: there are allowed and is prohibited by the proposition and certainarguments